2021
DOI: 10.3390/w13060868
|View full text |Cite
|
Sign up to set email alerts
|

Single and Competitive Adsorption Behaviors of Cu2+, Pb2+ and Zn2+ on the Biochar and Magnetic Biochar of Pomelo Peel in Aqueous Solution

Abstract: As an environment-friendly material, biochar has been used to remove heavy metals from wastewater, and the development of cost-effective biochar has been an emerging trend. However, limited studies consider the competitive adsorption of co-existing metals and the separation efficiency of absorbent and solution after adsorption. In this study, pomelo peel was used to prepare biochar (BC) and magnetic biochar (MBC) at different temperatures. Then, the physicochemical properties of the biochars were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…However, Pb­(II) cations are hydrated in water and thus have a total diameter of 8.02 Å with their hydration shell, which might have hindered their diffusion into the UiO-66­(COOH) 2 porous structure . This could mean that most of the adsorption took place on the outer surface of the MOFs and not inside the porous structure, which marginalizes the effect of the surface area and pore volume of the MOFs and the ionic diameter of the pollutant . This could be especially true given the small particle size of the UiO-66­(COOH) 2 samples, as could be seen in the SEM images in Figure S7, which increases the level of the external surface area of the adsorbent relative to the internal one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Pb­(II) cations are hydrated in water and thus have a total diameter of 8.02 Å with their hydration shell, which might have hindered their diffusion into the UiO-66­(COOH) 2 porous structure . This could mean that most of the adsorption took place on the outer surface of the MOFs and not inside the porous structure, which marginalizes the effect of the surface area and pore volume of the MOFs and the ionic diameter of the pollutant . This could be especially true given the small particle size of the UiO-66­(COOH) 2 samples, as could be seen in the SEM images in Figure S7, which increases the level of the external surface area of the adsorbent relative to the internal one.…”
Section: Resultsmentioning
confidence: 99%
“…58 This could mean that most of the adsorption took place on the outer surface of the MOFs and not inside the porous structure, which marginalizes the effect of the surface area and pore volume of the MOFs and the ionic diameter of the pollutant. 59 This could be especially true given the small particle size of the UiO-66(COOH) 2 samples, as could be seen in the SEM images in Figure S7, which increases the level of the external surface area of the adsorbent relative to the internal one. Another possible scenario is the dehydration of Pb(II) ions, which could allow their diffusion in the UiO-66(COOH) 2 porous structure; in fact, the lower the hydration energy of a certain ion, the higher the possibility of it losing all, or part of, its hydration shell, increasing its adsorption.…”
Section: ■ Materials and Methodsmentioning
confidence: 95%
“…The thermodynamic fitting curve is shown in Figure 4 b, and the thermodynamic parameters are reported in Table 2 . According to Table 2 , the negative ΔG value increased with increasing temperature, showing that the adsorption process was more favorable at higher temperatures and implying that the adsorption process was chemisorption [ 9 ]. In addition, the positive ΔH value indicated that adsorption was endothermic.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant studies show that Cu(II) accumulation limits the growth and development of plants and causes a reduction in the fecundity of aquatic life [ 5 , 6 ]. Moreover, an enrichment of trace copper(II) in organisms can be achieved through the food web, leading to excessive intake of copper by people, which can evoke diarrhea, hepatic and renal dysfunctions, and severe mental and neurological illnesses [ 5 , 7 , 8 , 9 ]. Numerous approaches and techniques, including adsorption [ 10 ], membrane separation [ 11 ], electrocoagulation [ 12 ], chemical precipitation [ 13 ], and microbial treatment [ 14 ], have been used to remove copper ions from water.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-oil, biochar and pyrolytic gas are useful products formed during this process [ 1 ]. In this way, we can reduce the storage or incineration of such waste as fruit stones, nut shells, sawdust, corn cobs, sunflower husks, straw or herbal herbs [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%